The Influence of Social Responsibility in Employee Satisfaction Mediated by Corporate Image and Organizational Commitment - Wahidahwati, Wahidahwati; Fauzi, Adilla Nanda Citra (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020)DO - 10.24843/JIAB.2020.v15.i02.p07, 2020)
This study aims to examine the effect of corporate social responsibility on employee satisfaction that is mediated by corporate image and organizational commitment. This type of research is quantitative research with survey methods conducted by distributing questionnaires. The sample in this study was obtained using a convenience sampling method, which is based on the availability of elements and the ease of obtaining them. The object of this research was employees of PT PJB UP Gresik, with a total of 170 respondents. The results of this study indicate that corporate social responsibility has a positive effect on employee satisfaction, corporate image, and organizational commitment. Other results found that corporate image and organizational commitment had a positive effect on employee satisfaction. The final, result found that corporate image and organizational commitment succeeded in mediating the effect of corporate social responsibility on employee satisfaction.